2023
DOI: 10.1002/eji.202250248
|View full text |Cite
|
Sign up to set email alerts
|

Human intestinal organoids: Modeling gastrointestinal physiology and immunopathology — current applications and limitations

Peter Flood,
Naomi Hanrahan,
Ken Nally
et al.

Abstract: Human intestinal organoids are an ideal model system to study gastrointestinal physiology and immunopathology. Altered physiology and mucosal immune response are hallmarks of numerous intestinal functional and inflammatory diseases, including inflammatory bowel disease (IBD), coeliac disease, irritable bowel syndrome (IBS), and obesity. These conditions impact the normal epithelial functions of the intestine, such as absorption, barrier function, secretion, and host‐microbiome communication. They are accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Many genetic analyses have revealed that these "tumoroids" highly conserve their genomic landscape, making them a suitable source to investigate genotype-phenotype correlations and perform drug screening, confirming the importance of organoids in terms of biobanking and the subsequent development of precision medicine [35]. Gut organoid models are among the most developed and have been intensively described in recent reviews [36][37][38][39]. Colon organoids represent useful applications for the identification of potential drug targets in the treatment of genetic disorders.…”
Section: Biomedical Applicationsmentioning
confidence: 98%
“…Many genetic analyses have revealed that these "tumoroids" highly conserve their genomic landscape, making them a suitable source to investigate genotype-phenotype correlations and perform drug screening, confirming the importance of organoids in terms of biobanking and the subsequent development of precision medicine [35]. Gut organoid models are among the most developed and have been intensively described in recent reviews [36][37][38][39]. Colon organoids represent useful applications for the identification of potential drug targets in the treatment of genetic disorders.…”
Section: Biomedical Applicationsmentioning
confidence: 98%
“…The differentiation medium is based on the expansion medium but lacks components such as Wnt family member 3A (WNT3A). It is used to induce the transformation of stem cells into diverse terminally differentiated colonic epithelial cell lineages ( Flood et al, 2023 ).…”
Section: Application Of Organoids In Ibdmentioning
confidence: 99%
“…Considering that the intestinal tract is composed of various cell types, including absorptive epithelial cells, goblet cells, Paneth cells, enteroendocrine cells, BEST4 cells, and intestinal stem cells [12,13], it may be difficult to accurately reproduce the response and function of the intestinal tract when relying solely on cell lines composed of a single cell type. Intestinal organoids, which can self-organize in three dimensions and reproduce the heterogeneity and behavior of the intestinal mucosa, are attractive tools to study in vitro the complex interactions between the different cell types and foreign agents, such as commensal or pathogenic microorganisms [14,15]. Several swine intestinal organoids have been constructed, which has allowed functional evaluations and viral infection studies [16][17][18], bridging the gap between in vitro and in vivo studies in pigs.…”
Section: Introductionmentioning
confidence: 99%